The Transtheoretical model's processes of change in the heart of a physical activity intervention: A series of n-of-1. (July 2023) - Lapointe, Josyanne; Comtois, Alain-Steve; Romain, Ahmed-Jérôme; Bernard, Paquito
Abstract: The objectives were a) to test whether a Processes of Change (POC)-personalized Transtheoretical model (TTM)-based intervention could increase physical activity (PA) among inactive adults, and b) to examine whether the intervention increased the level of TTM theoretical constructs. The following hypotheses were formulated: 1) PA levels will be significantly higher during and after the intervention in comparison to baseline measures; 2) the level of targeted POCs will increase during the intervention; 3) non targeted POCs will stay stable, and 4) self-efficacy and decisional balance levels will increase during the intervention. A series of N-of-1 with A (1 to 2-week)-B(10-week)-A'(2-week) design were conducted with 12 inactive adults. Behavioral counselors used behavior change techniques to target TTM constructs and supervise PA. Interventions were individualized based on the 5 POCs with the lowest pre-intervention level. Device-based and subjective PA along with TTM measures were collected weekly online. PA data were analyzed with piecewise linear models. A visual analysis was run to examine the TTM constructs. Device, self-reported and TTM data were available for five, seven and five participants, respectively. A significant self-reported PA increase for six participants was found during the phase B and A2. A significant device-measured PA increase was observed in two participants during the study. A substantial increase of targeted POC from baseline for all participants with available data was observed. This study provides the first evidence of behavioral and psychological effects of a POC-personalized TTM-based intervention in inactive adults. Highlights: This Processes of Change-personalized Transtheoretical model-based intervention constitutes a replicable intervention. A personalized TTM-based intervention using processes of change levels was tested. This intervention increased physical activity levels for most participants.